RANCANG BANGUN SISTEM INFORMASI MARKETPLACE PENYEWAAN LAPANGAN FUTSAL BERBASIS WEB - Putu sidi arta; Anak Agung Ayu Putri Ardyanti; I Gede Juliana Eka Putra (Jurnal Teknologi dan Manajemen Informatika, 2018)
The market application of these futsal fields is to provide futsal tenants in determining field rentals by providing detailed information on each existing futsal field provider and also to help tenants of futsal field in getting real time information in real time, providing facilities in doing scheduling process futsal field without having to come directly to place futsal. Making this application is done by Waterfall method. This application is implemented with Codeigniter framework, and made with PHP programming language, and MySQL as database, and for system testing method using black box testing. This application can be done by 3 users, namely admin, provider and tenant. Admins can manage providers and tenants. Providers can manage detailed information provided, field data, rental rates, tournament info, info together, field quality info and field facility info. Tenants can choose the exam schedule to be ordered, place a field order, confirm payment, and look for sparring opponents. DOI: https://doi.org/10.26905/jtmi.v4i2.2229